Muslim-Friendly Tourism Development in Taiwan: Tourist Needs, Halal Certification, and Stakeholder Readiness - Dian Adi Perdana; Do Tuyet Ngan (Perkumpulan Ahli Manajemen Dakwah Indonesia (PAMDI), 2026)
Purpose – This study aims to examine the development of Muslim-friendly tourism in Taiwan by synthesizing existing evidence on tourist needs, halal certification, destination image, and stakeholder readiness. As a non-Muslim destination actively targeting the growing Muslim travel market, Taiwan provides an important context for understanding how religiously sensitive tourism services can be developed within a multicultural environment. Design/methodology/approach – The study employs a systematic literature review approach guided by the PRISMA framework. Relevant publications were retrieved from the Scopus database using the keywords “Halal Tourism Taiwan,” “Islamic Tourism Taiwan,” and “Religious Tourism Taiwan.” The review focused on English-language journal articles and book chapters published between 2021 and 2026. Data were extracted through a structured summary table and analyzed using qualitative descriptive synthesis. Findings – The review reveals that Muslim tourists visiting Taiwan primarily expect access to halal food, prayer facilities, Islamic-compliant amenities, reliable halal information, and a welcoming social environment. Halal certification plays a critical role in building trust by reducing uncertainty and signaling compliance with Islamic requirements. Muslim-friendly attributes significantly strengthen both cognitive and affective destination image, although they do not directly determine travel decisions. The findings further indicate that Taiwan has demonstrated substantial stakeholder commitment through government initiatives, halal certification programs, and industry engagement. Nevertheless, challenges remain regarding the uneven availability of Muslim-friendly facilities, service standardization, and stakeholder coordination. Research implications – The findings provide practical insights for policymakers, tourism operators, and halal certification bodies seeking to strengthen Taiwan’s competitiveness in the Muslim tourism market through integrated destination management. Originality/value – This study contributes to the literature by integrating fragmented discussions on tourist needs, halal certification, destination image, and stakeholder readiness into a comprehensive framework for understanding Muslim-friendly tourism development in Taiwan.